Automated door gate for dam with IoT / Adib Muazzam Mohamad Sidek - Mohamad Sidek, Adib Muazzam (2024)
The Internet of Things (IoT)-based automatic door gate system for dam monitoring and control is a cutting-edge solution that increases dam safety and efficiency dramatically. This project uses IoT technology to provide remote monitoring and control of dam-related parameters. Water level sensors, a microprocessor or Programmable Logic Controller (PLC), a communication module, and a motorised gate mechanism are key system components. The controller of the system analyses real-time data from water level sensors and uses established criteria to determine ideal gate placements. The motorised gate mechanism, which is powered by a motor or actuator, accurately responds to the controller's inputs, allowing for automated and exact control. Because remote access and control features have been integrated, authorised workers can monitor water levels and gate status in real time via a user friendly web-based dashboard or application. In the event of an emergency, the system is prepared to generate alarms and notifications, instantly contacting the appropriate persons or authorities. The strong security measures put in place ensure the system's integrity and prevent unauthorised access, protecting the entire infrastructure. Overall, this automated door gate system improves dam safety by enabling proactive monitoring, improved water flow control, and informed decision-making. The system's importance in modern dam management methods is highlighted by the minimization of risks connected with potential disasters and the optimisation of dam operations